Exploring the largest known Bronze Age earthworks in Europe through medium resolution multispectral satellite images - Agapiou, Athos; Hegyi, Alexandru; Gogâltan, Florin; Stavilă, Andrei; Sava, Victor; Sarris, Apostolos; Floca, Cristian; Dorogostaisky, Leonard (My University, 2023)
This study aims to provide new insights into Europe's largest known Bronze Age earthworks using open-access and freely distributed medium resolution satellite images. The most extensive Bronze Age fortifications in Europe, namely, the Corneşti-Iarcuri and Sântana – Cetatea Veche sites, were investigated through the Sentinel 2 and the newly launched Landsat 9 optical sensors. Image processing techniques were applied to both datasets, including vegetation indices, orthogonal spectral transformations, and pan-sharpening techniques. The final results revealed several known and unknown archaeological proxies by enhancing a number of linear and curved crop marks in the vicinity of the archaeological sites. Indeed, while previously implemented geophysical results confirmed some of these archaeological proxies, new findings (crop marks) were also revealed, representing archaeological structures that were unknown until now. The study's overall findings indicate that medium resolution satellite images can be used in appropriate areas with archaeological interest as a first step toward better understanding the broader context of an area. The findings addressed in this study have a direct impact on the non-invasive aspect of archaeology, as the methodology employed in this paper may be applied to various types of sites in southwestern Romania and beyond and might serve as a solid starting point for any archaeological project. Finally, this is the first elaboration of Landsat 9 intended for archaeological research and our study proves that its utility for archaeological and heritage purposes.
Keywords: Remote sensing archaeology; Crop mark; Archaeological prospection; Vegetation; Indices; Fortifications; Romania